Clinical, Biochemical, and Molecular Analyses of Medium-Chain Acyl-CoA Dehydrogenase Deficiency in Chinese Patients - Gong, Zhuwen; Liang, Lili; Qiu, Wenjuan; Zhang, Huiwen; Ye, Jun; Wang, Yu; Ji, Wenjun; Chen, Ting; Gu, Xuefan; Han, Lianshu (Frontiers in Genetics, 2021)
Objective: Medium-chain acyl-CoA dehydrogenase deficiency is a rare inherited metabolic disorder of fatty acid β-oxidation. The present study aimed to evaluate clinical and biochemical manifestations and the mutation spectrum of this disorder in a large cohort of Chinese patients. Methods: A total of 24 patients was enrolled, and blood acylcarnitine and urinary organic acid levels were measured by tandem mass spectrometry and gas chromatography-mass spectrometry, respectively. Mutations in the ACADM gene were detected by Sanger or the next-generation sequencing. Clinical progression, acylcarnitine spectra, and mutations were analyzed and described in detail. Results: Among the 24 patients, 6 cases were diagnosed because of disease onset with symptoms such as vomiting, diarrhea, convulsion, and hypoglycemia; 18 patients without symptoms were diagnosed by newborn screening. All patients accepted treatment after diagnosis developed normal intelligence and physique. The concentrations of octanoylcarnitine, the octanoylcarnitine/decanoylcarnitine ratio, and the octanoylcarnitine/acetylcarnitine ratio in the blood and urinary dicarboxylic acid concentrations were consistently elevated. Blood biomarkers failed to decrease after treatment. DNA sequencing revealed 7 known and 17 novel mutations in the ACADM gene of patients. Mutation p.T150Rfs*4 was most frequent, followed by p.R31C, p.F103Y, p.I223T, p.G362E, and c.387+1delG. Conclusion: Despite biochemical abnormalities, medium-chain acyl-CoA dehydrogenase deficiency showed relatively mild clinical phenotypes with low mortality and optimistic prognoses in China. Newborn screening is crucial for early diagnosis, treatment, and prognosis. Key Words ACADM gene, Medium-chain acyl-CoA dehydrogenase deficiency, Newborn screening, octanoylcarnitine, tandem mass spectrometry.